(untitled) (Archives of Pediatrics of Uruguay, 2021)
Introduction: congenital heart disease (CHD) is a frequent pathology among children. It may cause significant morbidity and mortality during childhood. These are complex patients, who require a comprehensive approach and an interdisciplinary team. Objective: to describe the epidemiological, clinical and evolutionary characteristics of children with CHD assisted in the Cardiology Department of the Children Hospital-CHPR in 2015. Material and Methods: descriptive, retrospective study, review of clinical records of patients with CHD, hospitalized in the Cardiology Department of the Children’s Hospital PRHC in 2015. Epidemiological and clinical characteristics of patients were described. Results: 63 patients were hospitalized during the evaluated period, a total rate of 6.58/1.000 discharges. They had an average age of 23.8 months. Eight patients were diagnosed in the prenatal period, 54 presented non-cyanotic CHD. Twenty-four children had undergone surgical treatment, 13 had had corrective surgery. Malnutrition was diagnosed in 43% and it was more prevalent in cyanotic CHD carriers, complex defects, and chromosomopathies or other malformations. Conclusion: CHD represented a small percentage of the children who required hospitalization at the PH-PRHC. The percentage of malnutrition was high. The study confirmed the significant morbidity and mortality of these patients. It is important to recognize the highest risk of these patients and act in a customized and timely fashion.